Mekanisme Pengawasan terhadap Lalu Lintas Barang Masuk ( Impor ) dan Barang Keluar ( Ekspor ) pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Type Madya Pabean C Mataram - Mintasrihardi Mintasrihardi; Baiq Rienelda; Elisyah Elisyah (Universitas Muhammadiyah Mataram, 2018)
International Trade is conducted by all countries in the World including Indonesia. Indonesia conducts international trade with export goods import activities. The benefits of doing this activity one of them increase the state revenue. Any export activity of imported goods will result in customs duties. Technically, the importation process involves a lot of interests or parties, be it activities before the goods arrive, the process at the time of the goods arrived, the process of customs clearence, until the goods release process arrived. As good as any system that is used if it is not supported by a clean or professional apparatus plus parties who try to take advantage of existing regulatory weaknesses for personal benefit, of course the system will not be able to run well or even in vain. In this case, effective supervision of customs and customs authorities in carrying out the monitoring tasks of the goods. The purpose of this study is to describe the monitoring mechanisms on the export and import of goods and to determine what factors influence the control of customs. This research is qualitative research with descriptive approach. In this case the researcher describes the monitoring mechanism to the traffic of export and import goods conducted by Customs and Excise of Mataram. Therefore, researchers conducted observations and interviews then analyzed it with data collection, data reduction, data display, and conclusions. From the analysis result, it is found that the monitoring mechanism to import export traffic conducted by KPPBC TMP C mataram is in accordance with the rules of invitation begins with gathering information from intelligence, document research, physical inspection, determining the path to goods passing through customs area and reporting supervision results to the center on a regular basis.